Cognitive Ergonomics on Employee Wellbeing: A Literature Review (The Journal of Economic Concerns, 2022)
Ergonomics is a strategy to reduce occupational disease rates and improving general working conditions for employees in order to improve productivity. Employee participation is often suggested to improve employees’ relations to the organization. Research shows that ergonomics adoption on workplace to enhance the productivity level by reducing health related problem and building employee friendly work environment is milestone to enhance employee performance. However, it is less known in context of Nepal. This study aims to explore cognitive ergonomics on employee wellbeing. For this study, research papers are exhaustively selected from scientific databases like Scopus, Web of Science, Science Direct and Google Scholar by developing criteria for each component to ensure the idea goes in-depth and analyzes the roles of the importance of cognitive ergonomics in promoting employee performance. In the process of paper selection, we set a criterion that the paper should directly or indirectly comprise cognitive ergonomics on employee wellbeing. The papers available in the database from 2000 to 2022 are mostly reviewed in order to complete this study. This study concludes that cognitive ergonomics is a subset of the greater subject of human factors and ergonomic sciences; however, it is still a relatively untapped resource for enhancing employee wellbeing. If planned effectively, cognitive ergonomics may make major contributions to increasing job performance, lean operations, productivity, and, ultimately, establishing safer and healthier workplaces in the industry.